Biofilm Production and Antibiotic Resistance in Clinical Isolates of Acinetobacter Species - Bhandari, Kabita; Chhunju, Sabina; Nayaju, Tulsa; Angbuhang, Khadga Bikram; Prajapati, Krishna Govinda; Upreti, Milan Kumar (Tribhuvan University Journal of Microbiology, 2023)
Objective: To study the occurrence of the biofilm producing Acinetobacter spp. from different clinical specimens and to assess the antibiotic susceptibility pattern of Acinetobacter species. Methods: This study was conducted at B&B Hospital Pvt. Ltd., Lalitpur, Nepal from February to September 2018. Various specimens including pus, sputum, urine, catheter tips, body fluids (bile, peritoneal fluid, CSF), suction tube, and blood were collected from the patients (n=5141) visiting B&B hospital. The bacterial isolates were subjected to antibiotic susceptibility testing and Acinetobacter spp. isolates were subjected to biofilm detection by microtiter plate method. Results: Out of 5141 specimens, 1179 (23%) were culture positive. Escherichia coli (40.8%) was found to be the predominant organism. A total of 83 isolates of Acinetobacter spp. were isolated among which 76(91.57%) were biofilm producers. Biofilm producing isolates of Acinetobacter spp. were found more resistant to the tested antibiotics than non- biofilm producing Acinetobacter spp. Conclusion: Most Acinetobacter spp. was capable of producing the biofilm. The biofilm producers were more resistant to the antibiotics under study which help to increase the resistivity nature of the bacteria. All of the isolates susceptible to colistin showed that the appropriate therapeutic option for infection caused by biofilm forming Acinetobacter spp.